On structural transformations of equations of perturbed motion for a certain class of dynamical systems - Koshlyakov, V. N. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
We consider a general method for structural transformations of one class of dynamical systems with gyroscopic forces, which enables us to remove gyroscopic terms from the original equations of perturbed motion. Without changing the qualitative properties of these equations, this method simplifies their investigation.